The effects of Aronia melanocarpa (AM) dietary supplementation on production performance, meat and egg quality, yolk volatile substances and antioxidant capacity of laying hens - Bo Jing; Haoyuan Wu; Zhenhua Liu; Hongmei Shang; Yuting Li; Zhouyu Jin; Hui Song (Journal of Applied Animal Research)
The effects of Aronia melanocarpa (AM) dietary supplementation on production performance, meat and egg quality, yolk volatile substances and antioxidant capacity of laying hens. A total of 480 Roman brown laying hens aged 25 wks were randomly divided into control, LAM, MAM and HAM groups and fed 0%, 1%, 4% and 7% AM, respectively. The results showed that AM dietary supplementation significantly increased the eggshell strength, significantly reduced 24 h dripping loss of breast and thigh muscles, and increased pH and 48 h dripping loss of breast and thigh muscles. Cooking loss was significantly lower only in the HAM group for breast muscle. The MAM group was able to significantly increase albumen height and Haugh units. Esters gradually decreased with the increase in AM content, and the addition of AM led to a decrease in alcoholic compounds but increased the contents of alkenes, alkanes, ketones, and acids. The dietary AM supplementation significantly reduces the MDA content of serum, liver, ovary, chest muscle, thigh muscle and yolk and increases the activities of GSH-Px, T-SOD and T-AOC. In summary, dietary AM supplementation could improve antioxidant capacity and expression of related genes, thereby improving meat and egg quality.